2000
DOI: 10.1007/s11745-000-541-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary phenolic compounds on tocopherol, cholesterol, and fatty acids in rats

Abstract: The effects of the phenolic compounds butylated hydroxytoluene (BHT), sesamin (S), curcumin (CU), and ferulic acid (FA) on plasma, liver, and lung concentrations of alpha- and gamma-tocopherols (T), on plasma and liver cholesterol, and on the fatty acid composition of liver lipids were studied in male Sprague-Dawley rats. Test compounds were given to rats ad libitum for 4 wk at 4 g/kg diet, in a diet low but adequate in vitamin E (36 mg/kg of gamma-T and 25 mg/kg of alpha-T) and containing 2 g/kg of cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 64 publications
11
88
3
Order By: Relevance
“…Aside from inhibition of lipid peroxidation, curcumin also decreased cholesterol levels in both the serum and brain tissue of mice (Soudamini et al, 1992). In rats, curcumin significantly decreased the total and very low-density lipoprotein (VLDL) and LDL cholesterol plasma concentrations (Kamal-Eldin et al, 2000).…”
Section: Cholesterol and Statinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from inhibition of lipid peroxidation, curcumin also decreased cholesterol levels in both the serum and brain tissue of mice (Soudamini et al, 1992). In rats, curcumin significantly decreased the total and very low-density lipoprotein (VLDL) and LDL cholesterol plasma concentrations (Kamal-Eldin et al, 2000).…”
Section: Cholesterol and Statinsmentioning
confidence: 99%
“…The underlying mechanism may involve reduced intestinal uptake of cholesterol (Kamal-Eldin et al, 2000). It has been established that tocotrienol, a vitamin E isoform, also has hypocholesterolaemic properties through a mechanism different from HMG-CoA reductase inhibition (Theriault et al, 1999).…”
Section: Cholesterol and Statinsmentioning
confidence: 99%
“…A clinical study in hypercholesterolemic patients reported that daily oral intake of sesamin for 4 weeks significantly decreased total and LDL cholesterol concentrations (Hirata et al, 1996). Sesamin as a dietary supplement administered in hyperlipidemic rats reduced plasma and liver total cholesterol and LDL cholesterol concentrations (Kamal-Eldin et al, 2000). The hypocholesterolemic effect of sesamin is probably through inhibition of intestinal absorption of cholesterol, increased excretion of cholesterol into bile and decreased activity of 3-hydroxy-3-methylglutaryl coenzyme A reductase (Hirose et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It also increases a-tocopherol level in rat plasma, suggesting in vivo interaction between curcumin and a-tocopherol. [71] The fatty acid content was found to increase after ethanol-induced liver damage is significantly decreased by curcumin treatment. [72] Curcumin causes the severity of pathological changes, and thus, it protects the damage of the heart from myocardial infarction.…”
Section: Action On Cardiovascular Systemmentioning
confidence: 99%